Clarithromycin-based Helicobacter pylori eradication therapy is not associated with higher treatment failure compared with non-clarithromycin-based regimens in a tertiary referral hospital in Switzerland (Swiss Medical Weekly, 2023)
BACKGROUND AND AIMS: Due to increasing antibiotic resistance, various Helicobacter pylori eradication regimens other than clarithromycin-based therapies have been proposed. However, detailed data on which therapies were employed and their eradication success is lacking. The purpose of this study was to analyse the response rates of different eradication therapy schemes.METHODS: In this retrospective cohort study, we analysed data of 1721 patients and included 608 patients undergoing H. pylori eradication therapy at the Department of Gastroenterology at the University Hospital Zurich between 2004 and 2018. The primary endpoint was the success rates of clarithromycin- and non-clarithromycin-containing H. pylori eradication regimens. We furthermore analysed factors with potential impact on the outcome of H. pylori eradication therapies, such as demographics, and smoking and social status.RESULTS: The most common therapy scheme (71% of all cases) was proton pump inhibitor (PPI)-amoxicillin-metronidazole, followed by PPI-amoxicillin-clarithromycin (21%) and PPI-metronidazole-clarithromycin (6%). There was no difference between the H. pylori eradication success of clarithromycin vs non-clarithromycin-containing therapies (71% vs 71%, p = 0.764).CONCLUSION: Despite increasing clarithromycin resistance globally, there was no difference in the eradication success of clarithromycin- and non-clarithromycin-containing therapy regimens in Switzerland. As varying triple therapies do not increase eradication rates in real-world settings, other primary therapy options such as quadruple therapies should be explored.